Teachers' Experiences of the Fort McMurray Wildfire: A Story of Surviving the Beast ... - Turcato, Whitney Cameron (Graduate Studies, 2018)
There are groups of professionals who experience emergency evacuations differently from others due to their public service roles. These groups of professionals (teachers, nurses, social workers, physicians, healthcare aides and more) are responsible for the safety and wellbeing of others during an emergency evacuation. Due to an increased amount of responsibility and lack of control over when and with whom they evacuate, emergency evacuations affect these public service communities differently than others in the larger community. In this philosophical hermeneutic inquiry, four high school teachers were interviewed following the 2016 Fort McMurray wildfire evacuation in order to expand our understanding of the experience of these professionals during times of crisis. Findings exposed the duality of roles that these communities are faced with in times of crisis as well as the importance of story and story telling in the recovery of individual and community. This research offers new insights into the effects of ...